Philippine multilingual medical thesaurus on anatomy: sense organs and diseases female urogenital and pregnancy complications in Iluko - Calipjo, Ken Mervin, T.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
The practice of medicine has been improving in the last 20 years with the discoveries in the biological sciences and advances in information technology. With the continued progress in the field of medicine the communication barrier between the medical professionals and patients due to differences in medical knowledge also continues to widen. In the local setting, the diversity of Philippine language brings complications in terms of communication between medical professionals and patients. To address this problem, the Philippine Multilingual Thesaurus project was conceived.
This study is part of the thesaurus project's collaborative efforts wherein it conducted a translation process of the US National Library of Medicine's "Medical Subject Headings" (MeSH) terms into Iluko. The medical terms, Anatomy: Sense Organs and Diseases: Female Urogenital and Pregnancy Complications, were acquired from the MeSH's website. These terms were translated through the use of Iluko dictionaries ranked according to its comprehensiveness and authoritativeness by Dr. Viveca V. Hernandez, a linguistics expert on Ilokano Morphology and Syntax from the Department of Linguistics, and Dr. Noemi Ulep-Rosal, an Iluko translator and professor of the Departamento ng Filipino at Panitikan ng Pilipinas, both from the University of the Philippines Diliman. On the other hand, seven respondents from the field of medicine and allied health sciences and five non-medical practitioners provided Iluko translations of these medical terms through a translation questionnaire sheet. Preliminary terms translated with the use of dictionaries were then compared and analysed with the twelve respondents through triangulation techniques. Formulated policies and guideline on thesauri construction were consulted and implemented in generating entry terms.
The study was able to translate 19 out of 109 deployed terms, or 17.43% of A09 Anatomy: Sense Organs have an Iluko equivalent, while 90 terms or 82.57% have no Iluko translation. Out of 335 terms on C13 Diseases: Female Urogenital and Pregnancy Complications, 166 ot 49.55%% have Iluko term equivalents while 50.45% comprises the part that has no Iluko translations.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject Headings -- Medicine -- Ilocos; Human Anatomy; Pregnancy Complications; Genitourinary organs -- Diseases